HISTOMORPHOMETRY STUDY OF ETAWAH CROSSBREED GOAT OVARY - Juliarta, I Gede Erik; Suwiti, Ni Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana; Vol. 12 No. 2 August 2020DO - 10.24843/bulvet.2020.v12.i02.p06, 2020)
The histomorphometry study of Etawah crossbreed ovaries has been carried out. A total of 64 left and right ovaries from PE goats at aged (12-36 months) and young (5-12 months) were taken from the Kampung Jawa Slaughterhouse, in Denpasar. Then next is made histological preparations and stained with Harris – Hematoxylin Eosin. The results showed that the histological structure of the ovary consisted of cortical and medullary layers, respectively. In the cortex layers were found follicular development, and there are blood vessels, loose connective tissue, and nerves in the medulla layers. There is no difference in the number of follicles in adult and young goats. There were no differences (P>0.05) of the right and left of the cortex and ovarian medulla. The ovarian cortex and medulla of adult PE goats are thicker (P<0.05) than a young.